Citizen participation and social control in the parishes of atahualpa, anconcito, san josé ancón, josé luis tamayo, and simón bolívar ”(Ecuador) - Panchana, Margarita; Peña, Humberto; Reyes, Anita; Cochea, Hermelinda (Journal of business and entrepreneurial studie, 2020)
The following work presents an investigation focused on citizen participation and social control, seeks to identify the real state of intervention of these two variables in matters of public interest, in the rural parishes of Atahualpa, Anconcito, San José de Ancón, José Luis Tamayo, and Simón Bolívar, of the province of Santa Elena, Ecuador, has a sample size of 150 people, by territorial jurisdiction, the survey is of an exploratory type, where a questionnaire was prepared and through the survey was collected reliable and relevant information. The results say: The Political Constitution (2008), Art. 95, citizens, individually or collectively, will participate in the main decision-making, related to public affairs. Article 204, the people are the constituent and first public authority oversight. The Organic Law on Citizen Participation (LOPC) generates the scenarios for social control and Accountability, and states that The slight knowledge of citizens regarding the Development and Territorial Planning Plan (PODT) of the parish of their jurisdiction, the low cognitive level with respect to the Organic Law on Citizen Participation (LOPC), and ignorance the majority of the Citizen Participation Mechanisms by the community, affect the low participation of constituents in the issues inherent in the development of the corresponding rural area. Finally, there is a great interest in trainings related to the themes set out in this section.